The country wife - Wycherley, William; Fujimura, Thomas H . (London : edward arnold ltd, 1965)
National Theatre, The Playwrights' company and Malcolm Wells and Daniel Blum present Julie Harris, Laurence Harvey, Pamela Brown in "The Country Wife," by William Wycherley, the English stage company production with Ernest Thesiger, John Moffatt, Maureen Quinney, Richard Easton, Paul Whitsun-Jones, Ludi Claire, Peter Donat, directed by George Devine, decor by Motley, music by Thomas Eastwood, associate producer Don LaSusa.
In: Richard L. Coe Theater Programs Collection (Library of Congress).